Features of the Synovium of Individuals at Risk of Developing Rheumatoid Arthritis: Implications for Understanding Preclinical Rheumatoid Arthritis. Issue 3 (March 2014) - de, M. J. H.; van de, M. G. H.; Ramwadhdoebe, T. H.; Hansson, M.; Landewé, R.; van der, C.; Maas, M.; Serre, G.; van, D.; Klareskog, L.; Gerlag, D. M.; van, L. G. M.; et al.
<x xml:space="preserve">Abstract</x> Objective Findings from previous studies have suggested that subclinical inflammation of the synovium does not coincide with the appearance of rheumatoid arthritis (RA)–specific autoantibodies. This study was undertaken to examine the relationship between the presence of autoantibodies, changes in the synovium, and development of arthritis over time in a markedly larger, prospective study. Methods Fifty‐five individuals who were IgM rheumatoid factor positive and/or anti–citrullinated protein antibody (ACPA) positive (detected by the anti–cyclic citrullinated peptide antibody test) and who were without any evidence of arthritis upon physical examination were included in the study. ACPAs were subsequently also detected using a multiplex chip‐based assay. All individuals underwent magnetic resonance imaging and mini‐arthroscopic synovial biopsy sampling of a knee joint at inclusion and were prospectively followed up. Proportional hazards regression analysis was performed to investigate whether changes in the synovium were associated with the onset of arthritis. Results Fifteen individuals (27%) developed arthritis after a median followup time of 13 months (interquartile range 6–27 months; range 1–47 months). No overt synovial inflammation was observed, but CD3+ T cell numbers in the biopsy tissue showed a borderline association with subsequent development of clinically manifest arthritis (hazard ratio 2.8, 95% confidence interval [95% CI] 0.9–9.1; P = 0.088). In addition, the presence of CD8+ T cells was associated with ACPA positivity (odds ratio [OR] 16.0, 95% CI 1.7–151.1) and with the total number of ACPAs present (OR 1.4, 95% CI 1.0–1.8). Conclusion These findings confirm and extend previous results showing the absence of clearcut synovial inflammation in individuals having systemic autoimmunity associated with RA. However, subtle infiltration by synovial T cells may precede the signs and symptoms of arthritis in preclinical RA.